MAKNA SPIRITUALITAS PADA PASIEN KANKER SERVIKS DALAM MENJALANI PROSES PENGOBATAN - Dewi " Septiani; Yulia Irvani Dewi; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research is to explore the meaning of spirituality in cervical cancer patients undergoing treatment process. Thisresearch used a qualitative method with descriptive phenomenology approach.The research  conducted in women cervical cancer at Arifin Achmad Pekanbaru Riau Province. Participants involved in research 3peoplewhowere by using purposive samplingtechniquestothe inclusion criteria. The study used interview guide. Analysisused was analysis thematic. The results of this study found that there are three themes, namely: spiritual change, spiritual activities were undertaken, and hopes for better. Based on these results, showing that nurses need to perform a spiritual assessment in patients with cervical cancer, and interventions to spiritual problems experienced by patients. Keywords: Cervical cancer, Spirituality, Treatment process